Evaluation of lipid profile, malondialdehyde, hemoglobin and ferritin in Iraqi women with polycystic ovarian syndrome - Shenta, Ashwaq A.; Al-Maliki, Abbas D.M.; Abou-Turab, Mufid K. (European Journal of Clinical and Experimental Medicine, 2025)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. The concept of polycystic ovarian syndrome (PCOS) is defined as a biochemical complex statement that affects many young and adult females (single and married). This case presents a variety of medical and biological concerns related to the reproductive system. The aim of the study was to investigate and estimate the levels of the lipid profile, malondialdehyde, hemoglobin and ferritin in women with PCOS. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Material and methods. Blood samples were collected from 180 women who were divided into 100 PCOS patients and 80 healthy women according to the variables of age and body mass index. Triglycerides (TG) levels were measured in blood sera by spectrophotometric method, total cholesterol (TC) levels were estimated using enzymatic methods and the high-density lipoprotein (HDL) was determined by the HDL-phosphotungstic acid precipitation method. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Results. Total cholesterol, triglyceride, low-density lipoproteins, and very low-density lipoproteins recorded a highly significant increase (p<0.001) whereas high-density lipoproteins decreased significantly (p<0.001) in women with PCOS women when compared to the control group depending on age and body mass index variables. The results showed that hemoglobin, ferritin and malondialdehyde levels increased significantly (p<0.001) in female PCOS compared to the healthy group according to age and body mass index variables. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;"> Conclusion. The importance of thorough medical management of PCOS includes minimizing oxidative stress, metabolic function, and lipid profiles for avoidance of chronic health conditions.